Lipoprotein composition regulates hepatic lipase cell-surface association and activity - Boucher, Jonathan G (University of Ottawa (Canada), 2007)
It is well established that high triacylglyceride (TG) and reduced high density lipoprotein (HDL) levels increase the risk of developing heart disease and atherosclerosis. It has been assumed that the hydrolysis of TG-rich lipoproteins by the enzymes hepatic lipase (HL) and lipoprotein lipase (LPL) is the major determinant of HDL concentrations in the bloodstream. However, data now indicate that HDL is not only a product of TG-rich lipoprotein hydrolysis but also plays an active role in the regulation of TG metabolism by both HL and LPL. Our laboratory has previously shown that HDL regulates the activity of HL by releasing the enzyme from the cell-surface and enhancing its hydrolytic activity. In this study, the factors regulating the ability of HDL to stimulate the cell-surface displacement of HL and control its activity were characterised. Using a Chinese hamster ovary cell line stably overexpressing human HL (CHO-hHL), it has been shown that incubation with HDL or apolipoprotein (apo) A-I alone can displace HL protein and activity as determined by HL immunoblot analysis and enzyme activity measurements. Incubation of different HDL sub-species with CHO-hHL cells showed that the larger and less dense HDL particles were more effective at displacing HL from the surface than the smaller, more dense HDL species. The ability of the different classes of HDL to regulate very low density lipoprotein (VLDL) hydrolysis by HL in vitro was also evaluated. The larger, less dense HDL were stimulatory, while the smaller, more dense HDL particles were inhibitory to VLDL hydrolysis by HL. The hydrolytic activity of HL is well known to be regulated by lipoprotein structure and composition. The effects of the apoA-I and apoA-II content of HDL particles on the structure, hydrolysis and displacement of HL were investigated. Synthetic HDL containing apoA-I (LpA-I) or apoA-II (LpA-II) and various lipids were generated and used as model HDL particles with well-defined lipid and protein compositions. LpA-I containing apoA-II (LpA-IIA-II) significantly inhibited DG hydrolysis in DG-rich LpA-I particles and phospholipid hydrolysis in TG-rich LpA-I complexes. The effect of HDL apoA-I and apoA-II content on HL-mediated VLDL hydrolysis was also determined. While LpA-I inhibited VLDL hydrolysis, addition of apoA-II showed enhanced inhibition of HL-mediated VLDL lipolysis. The effect of apoA-II on the ability of HDL to displace cell-surface HL was also evaluated. LpA-I particles containing apoA-II (LpA-IIA-II) significantly stimulated the ability of this particle to displace cell-surface HL by approximately 2.3-fold compared to native HDL or LpA-I without apoA-II. The effects of phospholipid composition on lipoprotein electrostatic properties, HL activity and cell-surface displacement were also investigated. Enrichment of serum or lipoproteins with the anionic lipids oleic acid, phosphatidylinositol (PI), phosphatidylserine (PS) or phosphatidic acid (PA) increased the negative charge of all lipoprotein classes and stimulated HL-mediated lipid hydrolysis. Lipoproteins enriched with anionic lipids showed enhanced TG hydrolysis, while phospholipid hydrolysis was negligible. The electrostatic properties of HDL also had an effect on the hydrolysis of VLDL by HL. Enrichment of HDL with PI significantly stimulated VLDL-TG hydrolysis by HL relative to HDL enriched with the uncharged phosphatidylcholine (PC). HL-lipoprotein interactions were quantified in order to determine whether HDL charge affects the association of HL with HDL and VLDL. Under normal conditions, HL preferentially associates with HDL while only small amounts of HL bind to VLDL. In contrast, PI-enrichment of HDL reduces the binding of HL with HDL and VLDL. The role of lipoprotein charge on the ability of HDL to displace HL from the surface of CHO-hHL cells was also evaluated. Increasing the negative charge of HDL by enriching with PI significantly inhibited the ability of this lipoprotein to displace cell-surface HL. However, enrichment of HDL with the less charged PC also reduced its ability to displace HL into the media of CHO-hHL cells. These data suggest that HDL charge does not significantly affect the ability of HDL to displace HL from the cell surface. It now appears that factors affecting HL displacement and HL-lipoprotein association regulate lipid hydrolysis by this enzyme. ApoA-II is well known to enhance the binding of HL to HDL and it is now clear that tighter binding of the enzyme is inhibitory to HL-mediated lipolysis. The tighter binding of apoA-II to HL also appears to enhance its ability to displace cell-surface HL. In contrast, increasing the negative charge of lipoproteins stimulates hydrolysis by reducing the association of HL with lipoproteins. A reduction in the association between HL and HDL may be responsible for the relative inability of negatively charged HDL particles to displace cell-surface HL. Thus, HDL controls the hydrolysis of VLDL by directly affecting the displacement and inter-lipoprotein association of HL. Lipoprotein composition and charge appear to be important regulators of the binding, displacement and activity of HL.
Keywords: Chemistry, Biochemistry.